Explore the Role of Different Cognitive Functions in Education - Asaad , Mohammed Ahmed Babker (Journal of Education and Practice, 2023)
Purpose: The purpose of this review was to focus on the role of different cognitive functions in education. Methodology: The paper used a desk study review methodology where relevant empirical literature was reviewed to identify main themes and to extract knowledge gaps. Findings: Cognitive functions can play a significant role in improving education systems by informing instructional design, assessment methods, and student support strategies. It was concluded that application of cognitive functions in education involves utilising the understanding of how the brain processes information to inform instructional design, assessment methods, and student support strategies. Unique Contribution to Theory, Policy and Practice: Interventions targeting specific cognitive functions, such as memory-enhancing strategies or attention-focusing techniques, can be used to support students with learning difficulties. Overall, the application of cognitive functions in education can lead to more effective and engaging instruction, personalised learning experiences, and improved academic performance for students.